2016
DOI: 10.1016/j.healthplace.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Changing spatial patterns and increasing rurality of HIV prevalence in the Democratic Republic of the Congo between 2007 and 2013

Abstract: The Democratic Republic of the Congo (DRC) has one of the lowest HIV prevalence in sub-Saharan Africa, estimated at 1.1% [0.9-1.3] of adults aged 15-49 in 2013 (UNAIDS). Within the 2 million km2 country, however, there exists spatial variation in HIV prevalence, with the highest HIV prevalence observed in the large cities of Kinshasa and Lubumbashi. Globally, HIV is an increasingly rural disease, diffusing outwards from urban centers of high HIV prevalence to places where HIV was previously absent or present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
3
16
0
Order By: Relevance
“…More complex methods, such as kriging or Bayesian hierarchical modeling with a spatial component, used statistical models to predict HIV prevalence [24, 27, 32, 3437, 3941]. Software use varied by method, with IDW and kriging maps typically created using ArcGIS [38], kernel density smoothing done in BayesX [18] or Idrisi [23], and Bayesian modeling done in R [35, 36], WinBUGS [39, 40], or OpenBUGS [27] (see S1 Table).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More complex methods, such as kriging or Bayesian hierarchical modeling with a spatial component, used statistical models to predict HIV prevalence [24, 27, 32, 3437, 3941]. Software use varied by method, with IDW and kriging maps typically created using ArcGIS [38], kernel density smoothing done in BayesX [18] or Idrisi [23], and Bayesian modeling done in R [35, 36], WinBUGS [39, 40], or OpenBUGS [27] (see S1 Table).…”
Section: Resultsmentioning
confidence: 99%
“…Detailed smoothed maps also enabled visual comparisons of the spatial patterns of HIV over time periods [17, 29, 34, 35], or between various subgroups of the population, such as men and women or those living in sero-discordant partnerships and those not [19, 28, 36, 39]. GIS software also helped validate HIV prevalence estimates from antenatal care surveillance against population-based survey estimates, which are more comprehensive, but more resource-intensive, by comparing data between the two sources at similar locations [43, 44].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ordinary kriging interpolation was widely used to estimate the extent and geographical distribution for infectious diseases such as HIV, West Nile Disease and Dengue fever [ 25 27 ]. Kriging is an effective supplement for regular case surveillance, which depends on the medical personnel report.…”
Section: Discussionmentioning
confidence: 99%
“…Despite substantial reductions in the national HIV prevalence for several sub-Saharan Africa (SSA) countries, recent studies have identified important disparities in the decline of HIV prevalence at subnational levels [1][2][3] . Results from these studies suggest that the observed declines in HIV prevalence reflect aggregate measures at the national level, obscuring local variations in the spatio-temporal dynamics of the HIV epidemic.…”
mentioning
confidence: 99%